Complaints and accusations of bad governmental practices against Francisco de Sande, Governor and Captain General of the Philippine Islands: 1575-1580. (2019)
Following the recent historiographical debates regarding corruption in Hispanic America, the complaints and accusations against Francisco de Sande as Governor and Captain General of the Philippine Islands (1575-1580) will be described; this, before his return to New Spain as a Judge of the High Court of Mexico (Real Audiencia) and being promoted to president of the high court of the territory of Guatemala and then to the Kingdom of Granada. It will be pointed out that there is continuity in the accusations against him in all the latitudes where he performed royal duties, in contrast to the national historiographies which have affirmed that his bad practices only took place in some territories. Finally, an investigation is opened into the relational capital of Francisco de Sande in order to understand the dynamics of the corruption at this early stage.